2018
DOI: 10.1002/14651858.cd013229
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural interventions for smoking cessation: an overview and network meta-analysis

Abstract: Behavioural interventions for smoking cessation: an overview and network meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 32 publications
1
62
0
3
Order By: Relevance
“…When we undertook a meta-analysis, we found that bespoke person-based smoking cessation interventions for people with SMI were more effective than usual care across all time-points. This is in line with previous reviews suggesting that smoking cessation interventions are effective in people with mental health problems (but not exclusively SMI) [13] and the general population [40]. The largest of the three trials (n = 526) in this meta-analysis was at low risk of bias (there were some concerns for the other two), meaning that we are reasonably confident in our conclusion.…”
Section: Discussionsupporting
confidence: 90%
“…When we undertook a meta-analysis, we found that bespoke person-based smoking cessation interventions for people with SMI were more effective than usual care across all time-points. This is in line with previous reviews suggesting that smoking cessation interventions are effective in people with mental health problems (but not exclusively SMI) [13] and the general population [40]. The largest of the three trials (n = 526) in this meta-analysis was at low risk of bias (there were some concerns for the other two), meaning that we are reasonably confident in our conclusion.…”
Section: Discussionsupporting
confidence: 90%
“…Network meta-analyses have gained great importance in therapeutic research wherever a large number of CTs on different drugs are to be correlated. [5][6][7][8][9] This is currently particularly true in psoriasis, where a large number of approved drugs means that it is no longer possible to conduct complete clinical research with direct comparisons. Multiple comparisons are therefore used via bridge operators to create a comparable data situation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, interventions other than drug treatments were investigated, such as exercise in Alzheimer's disease 8 . A rising number of NMAs has also been used in current Cochrane reviews 9 . However, a surprisingly low number of meta‐studies investigating the quality and outcomes of different NMAs for one indication and type of intervention has been published 10,11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019 and 2020, CTAG published six new reviews and updated 15 previously published reviews Many of these reviews were updated as part of a National Institute for Health Research (NIHR)‐funded Cochrane programme grant in order to feed into an overview of reviews with a component network meta‐analysis of behavioural interventions for smoking cessation [11]. Others were updated at the request of NICE to inform guideline updates [12–14].…”
Section: Resultsmentioning
confidence: 99%